A randomized, crossover, placebo-controlled clinical trial to assess the sensitivity of the CRCDS Mini-Sim to the next-day residual effects of zopiclone. (June 2015) - Simen, Arthur A.; Gargano, Cynthia; Cha, Jang-Ho; Drexel, Melissa; Bautmans, An; Heirman, Ingeborg; Laethem, Tine; Hochadel, Thomas; Gheyle, Lien; Bleys, Kim; Beals, Chan; Stoch, Aubrey; et al.
Objectives: We sought to validate Cognitive Research Corporation's Driving Simulator (CRCDS Mini-Sim) for studies of drug safety with respect to driving ability. Methods: A total of 30 healthy subjects were randomized to receive placebo or 7.5 mg zopiclone, a hypnotic known to impair driving, in random order during the 2 treatment periods of a 2 period crossover design. Results: Evening administration of 7.5 mg zopiclone increased next-day standard deviation of lateral lane position (SDLP) by 2.62 cm on average compared with evening administration of placebo, and caused significant effects on symmetry analysis. The magnitude of the change in SDLP is highly similar to changes previously observed using on-the-road driving methods. Conclusions: Further validation of the CRCDS Mini-Sim is warranted to develop this platform for drug safety studies.